Antibiotic resistance and enterotoxin gene profiles of Staphylococcus aureus isolated from raw milk in Iran - Shariatifar, M; Salavati-Hamedani, M; Rezaeian-Doloei, R; Rezaeigolestani, M; Mohsenzadeh, M (Journal of the Hellenic Veterinary Medical Society, 2023)
Staphylococcus aureus is a food-borne pathogen frequently isolated from raw milk in different parts of the world. The emergence of antibiotic resistant strains of S. aureus has become an important global public health issue. In spite of this problem, the contamination rate of raw milk with enterotoxigenic antibiotic resistant S. aureus strains has been rarely evaluated in Iran. This study aimed to evaluate the prevalence and antibiotic resistance of coagulase positive S. aureus strains isolated from bulk tank milk samples in Mashhad, and to analyze the frequency of genes encoding the staphylococcal enterotoxins (SEs). 250 milk samples were tested for S. aureus by the conventional plating method and PCR. The disc diffusion method was used to assess the antibiotic susceptibility of the isolated S. aureus. Finally, the frequency of the SEs encoding genes was determined by the PCR method. S. aureus was detected in 18.4% of the tested milk samples at mean concentrations of 3.5 × 105 CFU/ml. The results showed that 86.95% of the isolates were resistant to at least one antibiotic and the highest resistance was observed against penicillin, ampicillin and methicillin. In total, 71.74% of the studied bacteria had at least one of the SEs encoding genes, and sec and sea genes were the most prevalent ones. In conclusion, the prevalence of enterotoxigenic antibiotic-resistant S. aureus in the milk samples collected from Mashhad dairy farms proves that additional efforts must be devoted to implementing hygienic processes in dairy farms and controlling antibiotic usage as well.